Cross‐sectional and longitudinal associations of white matter hyperintensities and cortical thickness in the biomarkers of Alzheimer's Disease in Down Syndrome (ADDS) study: Neuroimaging / imaging and genetics. (7th December 2020) - Lao, Patrick J; Luo, Linggang; Igwe, Kay C; Rizvi, Batool; Sathishkumar, Mithra; Rosas, H. Diana; Lai, Florence; Mapstone, Mark; Head, Elizabeth; Silverman, Wayne; Lott, Ira T; Schupf, Nicole; et al.
Abstract: Background: There is a general consensus that cerebrovascular change plays a role in the clinical presentation of Alzheimer's disease (AD) but considerable debate about its role in disease pathogenesis. Adults with Down syndrome (DS), like those with autosomal dominant mutations for AD, develop AD pathology and symptoms by their 40s and 60s, respectively. Unlike the general population, individuals with DS have low prevalence of classical vascular risk factors, like hypertension, but high prevalence of cerebrovascular disease in AD. We examined the association of cerebrovascular disease and cortical thinning in adults with DS. Method: To date, 66 adults (50±7yrs, 38% women, 33% MCI‐DS/dementia) enrolled in the ADDS study have undergone longitudinal processing of MRI (1.3±2yrs follow‐up) and clinical evaluation at three US sites. The ADDS study is a natural history study investigating biomarkers relevant to the transition into dementia in older adults with DS. Participants were classified as cognitively‐stable, MCI‐DS, possible AD dementia, definite AD dementia, or indeterminate based on consensus conference diagnosis. Cerebrovascular disease was operationally‐defined as white matter hyperintensity (WMH) volume measured at baseline. Neurodegeneration was defined as cortical thickness, measured with FreeSurfer at baseline and follow‐up. We examined the association of baseline WMH with baseline and longitudinal [%/yr] cortical thickness. Result: Cross‐sectionally, there was higher cortical thickness in cognitively‐stable individuals in the parietal lobe compared with MCI‐DS/dementia (p=0.02). Higher global WMH was associated with lower global cortical thickness (p=0.004), mostly driven by parietal and frontal lobe WMH distributions. The association of WMH with global cortical thickness was stronger among MCI‐DS/dementia than in cognitively‐stable (interaction; p=0.04). Longitudinally, higher baseline global WMH was associated with faster cortical thinning in cognitively‐stable compared with MCI‐DS/dementia (interaction; p=0.02), such that there was observable cortical thinning with WMH in cognitively‐stable compared to little‐to‐no cortical thinning with WMH in MCI‐DS/dementia. Conclusion: Higher WMH burden is associated with lower cortical thickness in adults with DS, particularly in parietal lobe and among those with MCI‐DS/dementia. However, higher WMH burden is more strongly associated with cortical thinning in those who are cognitively‐stable, suggesting that effect of vascular disease on neurodegeneration occurs prior to the onset of cognitive symptoms.